ANALISIS KEBUTUHAN TENAGA KERJA RESERVASI TERHADAP PERENCANAAN PENGEMBANGAN SUMBER DAYA MANUSIA PADA CV. CAN TOUR & TRAVEL - Christina, Maya; Kusuma Negara, I Made; Suardana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata); Vol 3 No 1 (2015): Jurnal IPTA (July 2015), 2015)
Employment remains the fundamental probel faced by many countries including Indonesia. One of the efforts the Government of Indonesia in extending employment opportunities is to develop the tourism sector. Bali is one of the potential tourist destinastions and it needs to be marketed. Cooperation between the Travel Bureau with the provider of the accommodation or hotel is one of the ways the potential market and the most instrumental in the development of the company, namely human resources required or called by labor. CV. CAN Tour and Travel is one of the tourist industry in Bali trip with a number of guest handling that quite a lot. This research aims to know the availability of labor needs resevartion in order CV. CAN Tour and Travel development and also to find out how the workforce qualification is required. Determination technique using the key informant that was labor reservation CV. CAN Tour and Travel, while the base of the informant was CV. CAN Tour and Travel Manager. Data analysis technique used is the analysis of workload and workforce needs analysis. The research results obtained indicate that shortage of time working as many as 210 minutes. So the manpower needed by CV. CAN Tour and Travel is two people with the fact that there is only 1 nowaday. It can be seen from the burden of the work done in a day’s work and the workforce absences. So labor needs on the Reservation Department is supposed to be 3 people, with 2 staff 1 reservations and ticketing staff. It was necessary increase manpower in the Labour Departmen’s Reservation in the reservation and also training to develop the ability to work.
Keywords: Needs, Qualification, Developing